Equations differentielles a points singuliers irreguliers et phenomene de stokes en dimension 2 - Sabbah Claude (Paris Societe Mathematique de France, 2000)
The asymptotic theory of holomorphic linear differential equations of 1variable is understood & has recently been renewed by the theory of multisummation. However the asymptotic theory of holonomic differential systems of many complex variables is still
Keywords: Functions of complex variables